The impact of artificial intelligence on cloud accounting (Czech Journal of Multidisciplinary Innovations, 2024)
The research aims to study the possibility of artificial intelligence affecting cloud accounting and how to develop cloud accounting through artificial intelligence and whether this effect is reflected positively or negatively on cloud accounting, which the British Encyclopedia defined as Encyclopedia Britannica on Line. It defined the term cloud accounting as a method of activating application software and storing related data in central computer systems and providing access to customers or users via the Internet. As for artificial intelligence, it is an attempt to make the machine able to think like a human being by developing complex systems.